Synchronous Liver Resection, Cytoreductive Surgery, and Hyperthermic Intraperitoneal Chemotherapy for Colorectal Liver and Peritoneal Metastases: A Systematic Review and Meta-analysis. Issue 6 (18th January 2021) - Flood, Michael P.; Das, Atandrila A.; Soucisse, Mikael L.; Kong, Joseph; Ramsay, Robert G.; Michael, Michael; Loveday, Benjamin P.T.; Warrier, Satish K.; Heriot, Alexander G.
Abstract : Supplemental Digital Content is available in the text. Abstract : BACKGROUND: Synchronous liver resection, cytoreductive surgery, and hyperthermic intraperitoneal chemotherapy for colorectal liver and peritoneal metastases have traditionally been contraindicated. More recent clinical practice has begun to promote this aggressive treatment in select patients. OBJECTIVE: This study aimed to investigate the perioperative and oncological outcomes of patients undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy, with and without liver resection, in the management of metastatic colorectal cancer. DATA SOURCES: Medline, Embase, and Cochrane Library databases were searched up to July 2020. STUDY SELECTION: Cohort studies comparing outcomes following cytoreductive surgery and hyperthermic intraperitoneal chemotherapy with and without liver resection for metastatic colorectal cancer were reviewed. No randomized controlled trials were available. INTERVENTION: Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy with or without synchronous liver resection were compared. MAIN OUTCOME MEASURES: The primary outcome measures were perioperative mortality and major morbidity. Secondary outcomes included 3- and 5-year overall survival and 1- and 3-year disease-free survival. RESULTS: Fourteen studies fitted the inclusion criteria, with 8 studies included in the meta-analysis. On pooled analysis, there was no significant difference in perioperative morbidity and mortality between the two groups. Patients that underwent concomitant liver resection had worse 1- and 3-year disease-free survival and 3- and 5-year overall survival. LIMITATIONS: Only a limited number of studies were available, with a moderate degree of heterogeneity. CONCLUSIONS: The addition of synchronous liver resection to cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for the treatment of resectable metastatic colorectal cancer was not associated with increased perioperative major morbidity and mortality in comparison with cytoreduction and hyperthermic intraperitoneal chemotherapy alone. However, the presence of liver metastases was associated with inferior disease-free and overall survival. These data support the continued practice of liver resection, cytoreductive surgery, and hyperthermic intraperitoneal chemotherapy in the management of select patients with such stage IV disease.